P-065 Phenotype, genetic analysis and treatment strategy of acephalic spermatozoa. (30th June 2022) - Weina, L; Wenbing, Z; Huan, Z; Guangxiu, L; Ge, L; Gang, L
Abstract: Study question: Do severe acephalic spermatozoa syndrome (ASS) patients with different genes variants obtain good fertilization rate after intracytoplasmic sperm injection (ICSI)? Summary answer: Despite highly abnormal sperm morphology, severe ASS patients with SUN5, TSGA10 and PMFBP1 different variations have a favorable pregnancy outcome following ICSI. What is known already: ASS is a rare cause of infertility characterized by the production of two main subtypes: one type has small "pin-head" ends devoid of any nuclear material, and the other comprises spermatozoa with misaligned head-midpiece junctions. Many researchers have suggested that variants in TSGA10 without a proximal centriole might influence early embryonic development. Some case reports studies with very few cases showed that ICSI could help patients with ASS father children. Study design, size, duration: This retrospective cohort study included 14 infertile men with severe ASS and 100 fertile men in Reproductive and Genetic Hospital of CITIC-Xiangya in China, from January 2020 to December 2021. Participants/materials, setting, methods: Patients and fertile men were recruited respectively from Outpatient Department and Sperm bank of our hospital in China. 14 severe ASS were analyzed by whole exome sequencing. Mutational analysis in the 14 severe ASS and 100 fertile men were performed. Identified SUN5, TSGA10 and PMFBP1 variations were further investigated using bioinformatics, RT-PCR, Western Blot, indirect immunofluorescence assay, papanicolaou staining, CASA, transmission electron microscopy and ICSI treatments. Clinical data were collected from the fertility center. Main results and the role of chance: In 14 patients with severe acephalic spermatozoa, 16 homozygous or heterozygous variants were identified from SUN5, TSGA10 and PMFBP1 . We performed deep phenotyping in acephalic spermatozoa with different variants, and found that, other than the two major subtypes, multiple variations in different genes that affect sperm heads in humans produce diverse phenotypes with subtle differences. Our findings were supported by Papanicolaou staining, SEM and TEM analyses. The rates of fertilization, good-quality embryos and pregnancy for 13 patients following ICSI were 85.71% (174/203), 55.17% (96 /174) and 69.23% (9/13), respectively. There were no differences in ICSI results between ASS patients with different genes mutations. The defects of acephalic spermatozoa caused by different genetic variations may only affect the morphology of sperm. ICSI can be used in the treatment of acephalic spermatozoa and obtain favorable fertilization rate without affecting the quality of early embryos and clinical pregnancy outcome. For individuals with ASS, ICSI using intact spermatozoa (or separated heads and tails) is suggested. If no sperm heads in their ejaculate, the spermatozoa can be collected from the testes. Very few intact spermatozoa or loose sperm heads will be available, even if normal morphology of spermatozoa is 0% and 100% spermatozoa are acephalic. Limitations, reasons for caution: Only a small number ASS patients was available because of its rare incidence. Patients with ASS can be effectively treated with ICSI. However, the results in this study should be treated with caution, which involves the TSGA10, SUN5 and PMFBP1 genes and cannot be extrapolated to other genes. Wider implications of the findings: The identification of novel variants in SUN5, TSGA10 and PMFBP1 broadens the spectrum of ASS genetic causes. Our study is the first to thoroughly evaluate the phenotypes and pathogenic genotypes of patients with severe ASS in China. SUN5, TSGA10 and PMFBP1 mutation-associated male infertility can be overcome by ICSI. Trial registration number: kq2014032